Addition of long-distance heart procurement promotes changes in heart transplant waiting list status - Atik,Fernando Antibas (2014)
Objective: Evaluate the addition of long-distance heart procurement on a heart transplant program and the status of heart transplant recipients waiting list. Methods: Between September 2006 and October 2012, 72 patients were listed as heart transplant recipients. Heart transplant was performed in 41 (57%), death on the waiting list occurred in 26 (36%) and heart recovery occurred in 5 (7%). Initially, all transplants were performed with local donors. Long-distance, interstate heart procurement initiated in February 2011. Thirty (73%) transplants were performed with local donors and 11 (27%) with long-distance donors (mean distance=792 km±397). Results: Patients submitted to interstate heart procurement had greater ischemic times (212 min ± 32 versus 90 min±18; P<0.0001). Primary graft dysfunction (distance 9.1% versus local 26.7%; P=0.23) and 1 month and 12 months actuarial survival (distance 90.1% and 90.1% versus local 90% and 86.2%; P=0.65 log rank) were similar among groups. There were marked incremental transplant center volume (64.4% versus 40.7%, P=0.05) with a tendency on less waiting list times (median 1.5 month versus 2.4 months, P=0.18). There was a tendency on reduced waiting list mortality (28.9% versus 48.2%, P=0.09). Conclusion: Incorporation of long-distance heart procurement, despite being associated with longer ischemic times, does not increase morbidity and mortality rates after heart transplant. It enhances viable donor pool, and it may reduce waiting list recipient mortality as well as waiting time.